(untitled) - Bennett, Haley; 1989-; 1967-; Johnston, Kristen; Garrett, Brad; 1959; Lawrence, Marc; 1960-; William O. Van Arsdale, IV and Family Collection (Burbank, CA, 2007)
Alex Fletcher is a washed-up 80s pop star who has been reduced to working the nostalgia circuit of county fairs and amusement parks. The charismatic and talented musician gets a chance at a comeback when reigning pop diva Cora Corman invites him to write and record a duet with her. The only problem is that Alex has not written a song in years, he has never written lyrics, and whats worse, he has to come up with a hit in a matter of days. Sophie Fisher is Alexs beguilingly quirky plant lady, whose flair for words strikes a chord with the struggling songwriter. On the rebound from a bad relationship with the newly famous novelist Sloan Cates, Sophie is reluctant to collaborate with anyone, especially commitment-phobe Alex. As their chemistry heats up at the piano, Alex and Sophie will have to face their fears and the music if they want to find the love and success they both deserve.
Keywords: United States; Man-woman relationships; Drama; Vocal duets; Drama; Drama; Popular music; Drama; Composition (Music); Drama; United States; United States; Lyricists; Romantic comedy films; Romance films; Musical films; Comedy films